Autorregulation in Decision Makining: the impact of choice object on the innovativeness - Prado, Paulo Henrique Müller; Korelo, José Carlos; Lucena, Danielle Mantovani; Ribeiro, Eneida Bezerra Soares (Review of Business Management, 2011)
This study examines the impact of the choice goals on the consumer’s innovativeness in categories of products that constantly suffer innovations. The contribution of this research is to analyze the behaviour of innovations adoption from the perspective of the Regulatory Focus Theory. The first stage of data collection was qualitative, exploratory in nature, in order to adjust the instrument to collect data for the second stage, with quantitative orientation, which was descriptive and in the form of a non-probability survey. From consumer’s ownership of attributes (basic, intermediate and advanced) it was generated a scoring system for targeting groups of consumers in ";more innovative"; and ";less innovative"; by the cluster analysis. The analysis of the proposed model was done by a structural equation modelling. Besides the evidence of the relationship between the promotion goals and prevention goals, were confirmed (directly and indirectly) the impact of the Evaluation Costs, Justifiability, Confidence and Regret on Innovativeness behaviour, resulting in differences between the groups. However, the impact of avoiding the negative emotions resulting from the choice was not registered significantly on innovativeness behaviour. These results refer to discussions about the context analysis and the theoretical implications of the impact on self-regulation on consumer’s choice behaviour. Key words: Self-regulation. Choice goals. Innovativeness. Consumer behaviour.